Synthesis and Characterization of Schiff Base Complexes of Molybdenum(VI), Tungsten(VI) and Chromium(III) with Vanillin and Aspartic Acid - Jepa Malar, A.; Sankaranarayana Pillai, M. (Asian Journal of Chemistry, 2010)
Metal chelates of Mo(VI), W(VI) and Cr(III) with Schiff bases have been synthesized by the condensation of o-vanillin with aspartic acid and characterized by spectroscopic method. Coordination of azomethine nitrogen in the Schiff base of the metal has been proposed.